Amyloid precursor protein processing in human neurons with an allelic series of the PSEN1 intron 4 deletion mutation and total presenilin-1 knockout. Issue 1 (14th October 2019) - Arber, Charles; Villegas-Llerena, Claudio; Toombs, Jamie; Pocock, Jennifer M; Ryan, Natalie S; Fox, Nick C; Zetterberg, Henrik; Hardy, John; Wray, Selina
Abstract: Mutations in presenilin-1 ( PSEN1 ), encoding the catalytic subunit of the amyloid precursor protein-processing enzyme γ-secretase, cause familial Alzheimer's disease. However, the mechanism of disease is yet to be fully understood and it remains contentious whether mutations exert their effects predominantly through gain or loss of function. To address this question, we generated an isogenic allelic series for the PSEN1 mutation intron 4 deletion; represented by control, heterozygous and homozygous mutant induced pluripotent stem cells in addition to a presenilin-1 knockout line. Induced pluripotent stem cell-derived cortical neurons reveal reduced, yet detectable amyloid-beta levels in the presenilin-1 knockout line, and a mutant gene dosage-dependent defect in amyloid precursor protein processing in PSEN1 intron 4 deletion lines, consistent with reduced processivity of γ-secretase. The different effects of presenilin-1 knockout and the PSEN1 intron 4 deletion mutation on amyloid precursor protein-C99 fragment accumulation, nicastrin maturation and amyloid-beta peptide generation support distinct consequences of familial Alzheimer's disease-associated mutations and knockout of presenilin-1 on the function of γ-secretase. Abstract : We report the generation of an allelic, isogenic series for the familial Alzheimer's disease mutation PSEN1 intron 4 deletion as well as total presenilin-1 knockout. Amyloid-beta profiles follow a mutation dose-dependent pattern. Presenilin-1 knockout lines display distinct phenotypes from intron 4 deletion lines, including reduced mature nicastrin, arguing against a simple loss-of-function mechanism for familial Alzheimer's disease mutations. Graphical Abstract: